Increased asymmetric dimethylarginine in severe falciparum malaria: association with impaired nitric oxide bioavailability and fatal outcome. - Yeo, T; Lampah, D; Tjitra, E; Gitawati, R; Darcy, C; Jones, C; Kenangalem, E; McNeil, Y; Granger, D; Lopansri, B; Weinberg, J; Price, R; et al. (Public Library of Science, 2010)
Asymmetrical dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase (NOS), is a predictor of mortality in critical illness. Severe malaria (SM) is associated with decreased NO bioavailability, but the contribution of ADMA to the pathogenesis of impaired NO bioavailability and adverse outcomes in malaria is unknown. In adults with and without falciparum malaria, we tested the hypotheses that plasma ADMA would be: 1) increased in proportion to disease severity, 2) associated with impaired vascular and pulmonary NO bioavailability and 3) independently associated with increased mortality. We assessed plasma dimethylarginines, exhaled NO concentrations and endothelial function in 49 patients with SM, 78 with moderately severe malaria (MSM) and 19 healthy controls (HC). Repeat ADMA and endothelial function measurements were performed in patients with SM. Multivariable regression was used to assess the effect of ADMA on mortality and NO bioavailability. Plasma ADMA was increased in SM patients (0.85 microM; 95% CI 0.74-0.96) compared to those with MSM (0.54 microM; 95%CI 0.5-0.56) and HCs (0.64 microM; 95%CI 0.58-0.70; p<0.001). ADMA was an independent predictor of mortality in SM patients with each micromolar elevation increasing the odds of death 18 fold (95% CI 2.0-181; p = 0.01). ADMA was independently associated with decreased exhaled NO (r(s) = -0.31) and endothelial function (r(s) = -0.32) in all malaria patients, and with reduced exhaled NO (r(s) = -0.72) in those with SM. ADMA is increased in SM and associated with decreased vascular and pulmonary NO bioavailability. Inhibition of NOS by ADMA may contribute to increased mortality in severe malaria.